Cereal grain mineral micronutrient and soil chemistry data from GeoNutrition surveys in Ethiopia and Malawi - D. B. Kumssa; A. W. Mossa; T. Amede; E. L. Ander; E. H. Bailey; L. Botoman; C. Chagumaira; J. G. Chimungu; K. Davis; S. Gameda; S. M. Haefele; K. Hailu; et al. (Scientific Data, 2022)
Measurement(s) Trace Element • soil chemical properties Technology Type(s) Inductively-Coupled Plasma Mass Spectrometry Factor Type(s) Geography • Staple cereal crop Sample Characteristic - Organism Staple cereal food crops Sample Characteristic - Environment Smallholder farming Sample Characteristic - Location Ethiopia • Malawi